The Influence Of Motivation And Compensation On Employee Performance At The Lungkang Kule Sub-District Office, Kaur District - Saputri, Yudisti; E. G., Ida Ayu Made; Abi, Yudi Irawan (Universitas Dehasen Bengkulu, 2025)
The purpose of this study was to determine the effect of motivation and compensation on the performance of employees at the Lungkang Kule District Office, Kaur Regency. The population in this study were all employees of the Kaur Regency High Prosecutor's Office totaling 31 employees, with a sample size of 31 employees. The sampling technique was cluster sampling. The data analysis technique used multiple linear regression: Y = 23.319 + 0.166X1 + 0.015X2, meaning that if motivation and compensation were increased by 100%, employee performance would be worth 0.166 and 0.015 respectively. The results of the study showed simultaneously by comparing the Fcount value with Ftable, so that it was known that the Ftable value was 3.757> 3.16 and it can be concluded that motivation and compensation had a significant effect on employee performance at the Lungkang Kule District Office, Kaur Regency. Based on the partial test, it is known that motivation has a positive and significant effect on the performance of employees at the Lungkang Kule District Office, Kaur Regency with a sig value of 0.004 < alpha (0.05), while compensation has a positive and insignificant effect on the performance of the Lungkang Kule District Office, Kaur Regency with a sig value of 0.810 > alpha (0.05).